Book review: Adami, Christoph. The evolution of biological information. How evolution creates complexity, from viruses to brains - Tom Wilson (Information Research: An International Electronic Journal)
Adami, Christoph. The evolution of biological information. How evolution creates complexity, from viruses to brains. Princeton, NJ: Princeton University Press, 2024. xvii, 563p. ISBN 978-0-691-24114-2